Reorganization of Dynamic Network in Stroke Patients and Its Potential for Predicting Motor Recovery - Xiaomin Pang; Longquan Huang; Huahang He; Shaojun Xie; Jinfeng Huang; Xiaorong Ge; Tianqing Zheng; Liren Zhao; Ning Xu; Zhao Zhang (Neural Plasticity)
Conclusions: The reorganization of dynamic network configurations in stroke patients reveals crucial insights into the mechanisms of motor recovery. These findings suggest that metrics of dynamic network reorganization, particularly global network switching rate, may offer a robust predictor of motor recovery.